Aplikasi Pengelolaan Data Profil dan Konsentrasi Dosen - Wibowo, Hariyanto; Sulyono, Sulyono; Lestari, Sri; Miranda, Thesa (TEKNIKA, 2020)
The success of the education process is strongly influenced by the quality of human resources, in this case lecturers as educators. While each lecturer has the potential, expertise, qualifications, competency profile and experience that sometimes varies between one lecturer and another. Therefore the management of profile and concentration data is very much needed so that the department can know with certainty the abilities possessed by the lecturer. In the Department of Informatics the management of lecturer profile and concentration data has not been well managed. so this research proposes the Application of Data Management Profile and Concentration of Lecturers in the Informatics Engineering Department IIB Darmajaya by using a system development method that is prototype. The results of this study are expected to be utilized appropriately for policy making, both in terms of determining lecturers, lecturers, and determining membership peer group research, and also for filling accreditation form data and for display on the web of the Department of Informatics.